ANALISIS KEMAMPUAN LITERASI BACA TULIS SISWA SEKOLAH DASAR TERHADAP PENERAPAN KURIKULUM MERDEKA - Putri, Ragil Dian Purnama; Martaningsih, Sri Tutur; Lestari, Tri; Hermansyah, Agus Kichi (Universitas Tribhuwana Tunggadewi, 2025)
This study aims to evaluate the reading and writing literacy levels of elementary school students and to assess the extent to which the Independent Curriculum contributes to improving literacy in Gunungkidul Regency, located in the Special Region of Yogyakarta. This region is predominantly rural and faces challenges related to limited access and inadequate educational facilities. The lack of educational resources—such as quality reading materials, proper libraries, and technological infrastructure—poses a major obstacle to enhancing student literacy. The research employs a quantitative approach to analyze numerical data, emphasizing standardized data collection methods and utilizing statistical analysis to test hypotheses. This approach is intended to provide a comprehensive understanding of students' reading and writing literacy skills. The findings reveal that the implementation of the Independent Curriculum in elementary schools across the Gunungkidul area has not yet produced a significant impact on improving students' literacy skills. This is evident from the average test scores, which remain below the Minimum Completion Criteria (MCC) set by the schools: 65.6 in the control group and 61.4 in the experimental group. Therefore, it can be concluded that the reading and writing literacy levels of elementary school students in the region remain relatively low.